FERROELECTRIC PROPERTIES OF BaBi4Ti4O15 DOPED WITH Pb2+, Al3+, Ga3+, In3+, Ta5+ AURIVILLIUS PHASES - Afifah Rosyidah; Djulia Onggo; Khairurrijal Khairurrijal; Ismunandar Ismunandar (Universitas Gadjah Mada, 2009)
In recent years, the ferroelectric properties of aurivillius oxides have attracted interest and an extensive amount of work has been done toward the realization of their potential application in nonvolatile memories (FeRAM: ferroelectric random access memory). Recently, we have carried out computer simulation in atomic scale in order to predict the energies associated with the accommodation of aliovalent and isovalent dopants (Pb2+, Al3+, Ga3+, In3+, Ta5+) in the aurivillius structure of BaBi4Ti4O15. In this work, the predicted stable phases were synthesized using solid state reactions and their products then were characterized using powder X-ray diffraction method. The cell parameters were determined using Rietveld refinement in orthorhombic system with space group of A21am. Results from the ferroelectric properties measurement of BaBi4Ti4O15 were also presented. The cell parameters for BaBi4Ti4O15 doped with Pb2+, Al3+, Ga3+,In3+, Ta5+ were a = 5.47116(4) b = 5.45636(5) c = 41.8649(3) Å; a = 5.47104(4) b = 5.45634(4) c = 41.8640(3) Å; a = 5.47112(4) b = 5.45648(4) c = 41.8643(3) Å; a = 5.47111(4) b = 5.45645(5) c = 41.8649(3) Å; and a = 5.47134(4) b = 5.45588(4) c = 41.8639(5) Å. The ferroelectric properties measurement for BaBi4Ti4O15 doped with Pb2+, Al3+, Ga3+,In3+, Ta5+ showed that the Pr = 15.225 mC/cm2, Ec = 33.96 kV/cm; Pr = 15.925 mC/cm2, Ec = 35.724 kV/cm; Pr = 16.625 mC/cm2, Ec = 36.504 kV/cm; Pr = 15.57 mC/cm2, Ec = 32.925 kV/cm; Pr = 17.2827 mC/cm2, Ec = 37.44 kV/cm.